Causal associations between circulating protein ratios and drug resistance in papillary thyroid cancer: a Mendelian randomization study - Jiaqin Deng; Ming Yu; Yihua Gu; Yeqian Lai; Lihong Qiu (Discover Oncology)
Abstract Objective Circulating protein level ratios (CPLRs) may play a crucial role in tumor progression and drug resistance by mediating interactions within the tumor microenvironment. This study aims to investigate the causal associations between CPLRs and papillary thyroid cancer (PTC), focusing on their potential implications in drug resistance mechanisms. Methods Genetic data for 2821 CPLRs were obtained from the GWAS and FinnGen databases. Mendelian randomization (MR) analysis, using inverse variance weighting (IVW) as the primary method, was conducted to explore causality. Sensitivity analyses, including heterogeneity and pleiotropy tests, were performed to ensure the robustness of the results. Results Twelve CPLRs were identified as causally associated with PTC. Seven CPLRs, such as REG1A/TFF3 and LAT/SPARC, were associated with reduced PTC risk, potentially reflecting protective mechanisms. In contrast, five CPLRs, including MAD1L1/PSIP1 and CIAPIN1/TYMP, were linked to increased risk, suggesting their role in promoting drug resistance. Reverse MR analysis revealed no significant causal associations, reinforcing the directionality of these findings. Conclusion These findings highlight the relevance of CPLRs in the pathogenesis and drug resistance of PTC, providing insights into potential biomarkers and therapeutic targets. Future research could focus on translating these findings into strategies for personalized medicine and targeted treatment.